Resource of distance learning technology in the formation of the professional competence of specialists in document science and information activities - Yakymenko, Nataliia; Zndanova-Nedilko, Olena; Isaienko, Tetiana; Voshchenko, Viktoriia (International Journal of Engineering and Technology, 2018)
The peculiarities of installing distance learning into the process of formation of professional competence of specialists in document science and information activities are analyzed; the terms "distance learning" and "distance education", "e-learning" are characterized, their uniqueness being demonstrated; integral, general and special professional competences, which are formed in the process of distance learning are listed and characterized. It is emphasized in the article that the use of the distance learning system in the process of preparing specialists in documentation and information activities makes it possible to carry out quasi-professional activities.Â Â Â